Public financial management systems Indonesia key elements from a financial management perspective. (Public financial management systems., 2018)
Foreign aid to Indonesia takes the form of loans or grants. The loans can be made either to the government or to state-owned enterprises with a guarantee from the government. This report documents Indonesias financial management systems covering budgeting, funds flow monitoring and analysis, accounting and reporting, and auditing. It also provides insights into the quality of internal control systems, staff capacity, and information technology structure. The intent is to provide project teams and consultants with a better understanding of financial management systems during project preparation. Find out how high-quality financial management assessments support project implementation through the identification of key risks and enabling the implementation of mitigating actions and reforms.